Disuguaglianza economica nelle società preindustriali: cause ed effetti / Economic inequality in pre-industrial societies: causes and effect - Nigro, Giampiero (Datini Studies in Economic History, 2020)
In contrast to the debates of the past, which focused mainly on income inequality and the related elements of injustice, the recent interest in economic inequality focuses on its effects on economic growth and social development. New research is an important element of these recent debates: a historical approach that contextualizes inequality with reference to social relations, institutions, access to power and its cultural legitimacy can facilitate the understanding of the mechanisms that lead to inequality and its effects.